2006
DOI: 10.1149/1.2167950
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Properties of Eu[sup 2+]-Doped MAl[sub 2−x]Si[sub x]O[sub 4−x]N[sub x] (M=Ca, Sr, Ba) Conversion Phosphor for White LED Applications

Abstract: Undoped and Eu-doped MAl 2−x Si x O 4−x N x ͑M = Ca, Sr, Ba͒ were synthesized by a solid-state reaction method at 1300-1400°C under nitrogen-hydrogen atmosphere. The solubility of ͑SiN͒ + in MAl 2 O 4 was determined. Nitrogen can be incorporated into MAl 2 O 4 by replacement of ͑AlO͒ + by ͑SiN͒ + , whose amount of solubility depends on the M cation. The solubility of ͑SiN͒ + is very low in CaAl 2 O 4 and SrAl 2 O 4 lattices ͑x Ϸ 0.025 and 0.045, respectively͒, whereas a large amount of ͑SiN͒ + can be incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 30 publications
3
54
0
Order By: Relevance
“…As we all know, sunlight conversion film is made up of two parts, including matrix and sunlight conversion agent, in which the latter plays a critical role in the performance of sunlight conversion properties. For sunlight conversion agent, many kinds of phosphors have been reported such as CaS:Cu + (Zhang, Li, Chen, Xiao, & Sun 2004), CaAl 2 O 4 :Eu 2+ (Li & Hintzen, 2006) and Ba 3 MgSi 2 O 8 :Eu 2+ (He et al, 2009). Compared with these doped phosphor, carbon dots (CDs), which consists a fascinating class of fluorescence-based nanoparticles, have emerged as important fluorescence materials because of their excellent photostability, chemical stability, high biocompatibility, and cost-effective preparation (Qu, Wang, Lu, Liu, & Wang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As we all know, sunlight conversion film is made up of two parts, including matrix and sunlight conversion agent, in which the latter plays a critical role in the performance of sunlight conversion properties. For sunlight conversion agent, many kinds of phosphors have been reported such as CaS:Cu + (Zhang, Li, Chen, Xiao, & Sun 2004), CaAl 2 O 4 :Eu 2+ (Li & Hintzen, 2006) and Ba 3 MgSi 2 O 8 :Eu 2+ (He et al, 2009). Compared with these doped phosphor, carbon dots (CDs), which consists a fascinating class of fluorescence-based nanoparticles, have emerged as important fluorescence materials because of their excellent photostability, chemical stability, high biocompatibility, and cost-effective preparation (Qu, Wang, Lu, Liu, & Wang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, silicon nitride based compounds have been extensively studied as host lattices for phosphors, which exhibit unusual, interesting luminescence properties when activated by rare earth ions, such as M 2 Si 5 N 8 :Eu 2+ [1][2][3][4][5], M 2 Si 5 N 8 :Ce 3+ [6], MSi 2 O 2−␦ N 2+2/3␦ :Eu 2+ , Ce 3+ [7][8][9], CaSiN 2 :Eu 2+ [10], Ce 3+ [11], MgSiN 2 :Eu 2+ [12,13], MYSi 4 N 7 (M = Sr, Ba):Eu 2+ , Ce 3+ [14,15], MSi x Al 2−x O 4−x N x :Eu 2+ (M = Ca, Sr, Ba) [16], ␣-SiAlON:RE (RE = Eu 2+ , Ce 3+ , Yb 2+ , Tb 3+ , Pr 3+ , Sm 3+ ) [17][18][19][20][21][22][23], ␤-SiAlON:Eu 2+ [24], SrAlSi 5 O 2 N 7 :Eu 2+ [25], SrAl 2 SiO 3 N 2 :Eu 2+ [25], and CaAlSiN 3 :Eu 2+ [26]. Most importantly, these phosphors emit visible light efficiently under near-ultraviolet or blue light irradiation and have superior thermal and chemical stability to their oxide and sulfide counterparts, allowing them to be used as down-conversion luminescent materials for white light-emitting diodes (LEDs).…”
Section: Introductionmentioning
confidence: 99%
“…Because the valence state of an activator ion depends on the coordination environment, the photoluminescent properties of phosphors can be controlled by modifying the covalency and polarizability of activator−ligand bonds in phosphors [11][12][13][14]. Moreover, the fluoride lattice provides a high coordination number for doped rare earth ions, and the high ionicity of the rare-earth-fluorine bond results in a wide band gap, low vibrational energies, and low probability of inter-configurational transitions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the fluoride lattice provides a high coordination number for doped rare earth ions, and the high ionicity of the rare-earth-fluorine bond results in a wide band gap, low vibrational energies, and low probability of inter-configurational transitions [15]. It has been previously reported that incorporating Si 4+ −N 3− into Ce 3+ -or Eu 2+ -doped phosphors will lead to a red shift in the 4f−5d emission owing to the lower electronegativity of N 3− compared to O 2− [11,12] Sample Characterization. The crystalline phases of each sample were identified by powder X-ray diffraction (XRD) measurements using a XD-3 diffractometer (PERSEE) with a Cu Kα radiation source (λ = 0.154 nm).…”
Section: Introductionmentioning
confidence: 99%